2010
DOI: 10.1021/jp104534m
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Diffusion of Oligosaccharide Solutions: The Role of Chain Length and Structure

Abstract: We investigated the chain length dependence of the thermodiffusion behavior of oligosaccharides by the infrared thermal diffusion forced Rayleigh scattering (IR-TDFRS)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 41 publications
2
30
2
Order By: Relevance
“…Likewise, Brenner's 41 kinematic model of thermal diffusion for liquid and gases establishes that D T is proportional to the thermal expansion coefficient. This linear correlation has also been observed for sugar solutions 42,43 and for alkanes in organic solvent. 44 12 We used the same symbols as in Fig.…”
Section: A Thermal Expansionsupporting
confidence: 70%
“…Likewise, Brenner's 41 kinematic model of thermal diffusion for liquid and gases establishes that D T is proportional to the thermal expansion coefficient. This linear correlation has also been observed for sugar solutions 42,43 and for alkanes in organic solvent. 44 12 We used the same symbols as in Fig.…”
Section: A Thermal Expansionsupporting
confidence: 70%
“…Describing the chain length in terms of the persistence length l p , D T becomes constant when the chain length is of around two to three times l p . The chain length dependence of D T of alkanes 14 , polystyrene 23 , sugars 20 and also of glycols in aqueous solution 25 is already documented in literature. If we follow the argumentation of the simulation results we expect for glycols in ethanol a different behavior compared the aqueous solutions, because in contrast to water no hydration layer is formed.…”
Section: Introductionmentioning
confidence: 79%
“…Apart from low molecular weight mixtures also polymers solutions and colloidal suspensions in polar and non-polar solvents have been investigated [16][17][18] . For this study, the thermal expansion coefficient α and the kinematic viscosity ν are measured to compare to recent results on alkanes 15 and sugars 19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…This is probably a consequence of the difference in the ratio of thermal expansion coefficient α over viscosity η: the difference of the ratio between light and heavy water increases with increasing temperature [52,53]. Earlier studies have shown that the thermal diffusion coefficient is proportional to the ratio α/η [54,55]. This implies that the thermal diffusion coefficient becomes larger for systems which show a larger thermal expansion coefficient and which are less viscous.…”
Section: Influence Of D 2 Omentioning
confidence: 99%